Analisis Praktik Percaloan dalam Rekrutmen Anggota Kepolisian NKRI dan dampaknya Terhadap Kualitas Sumber Daya Manusia - Hilma Harmen; Hannes Inmanuel Sinaga; Jones Wahyu Simamora; Nesmada Putri Manullang; Novita Yanti Sari Aritonang; Pasaribu, Veri Sangap Tua (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
The practice of brokerage in the recruitment of members of the Indonesian National Police still occurs frequently and poses a serious problem, as it can undermine the selection process, which should be fair and merit-based. This typically occurs due to the high public interest in joining the police force, a situation exploited by certain individuals to seek personal gain through improper means. This study aims to understand how recruitment brokerage occurs and its impact on the quality of human resources within the police force. The method used is a qualitative approach, analyzing several cases that have occurred in the community. The findings indicate that recruitment brokerage can lower the competency of officers, weaken integrity and work ethics, and reduce professionalism in the performance of duties. Furthermore, this practice prevents genuinely more competent candidates from receiving equal opportunities, thereby hindering the development of high-quality human resources. Another consequence is a decline in public trust in the police institution. Therefore, more serious efforts are needed to enhance transparency and oversight so that the recruitment process can proceed effectively and produce high-quality officers.